The Role of Counseling Guidance in Gambling Prevention During The Covid-19 Pandemic in Pasaman Police Jurisdiction Region - Rio Fachrihadi (Advances in Police Science Research Journal, 2021)
This research coincides with the world condition that is being hit by the COVID-19 pandemic which has an impact on various fields of life including the economy so that social inequality occurs which results in unstable national security and order conditions. The social gap that occurs is that the crime in the Pasaman area is often the occurrence of gambling. The police provide counseling guidance as a pre-emptive effort in preventing gambling crimes, which in this case includes the maintenance of security and social order conditions. The purpose of this study was to analyze the role of guidance and counseling for Satbinmas and the influencing factors in preventing gambling crimes in Pasaman. This study uses a qualitative approach, data collection techniques through interviews, observations and document studies. By using management theory and crime prevention theory and the concepts used are the concept of counseling guidance, the concept of the covid-19 pandemic and the concept of gambling. The results of this study found that the implementation of counseling guidance activities was not optimal and there were still problems felt by Satbinmas members.